ANALISIS PUTUSAN HUKUM PERCERAIAN QABLA AL-DUKHUL PADA KAWIN PAKSA DI PENGADILAN AGAMA SINJAI KELAS II - Usnidar Arfah; Andi Muhammad Akmal; Istiqamah (Qadauna: Jurnal Ilmiah Mahasiswa Hukum Keluarga Islam, 2023)
The main problem in this research is how to analyze the legal decision regarding qabla al-dukhul divorce in forced marriage at the Class II Sinjai Religious Court. This research is a type of field research with a normative juridical approach. The results of the research show that the factors behind divorce due to forced marriage at the Sinjai Religious Court are generally caused by two factors, namely, the unwillingness to enter into marriage and the factor of infidelity. Regarding the divorce trial mechanism for qabla al-dukhul due to forced marriage at the Class II Sinjai Religious Court, it is generally the same as the divorce trial mechanism, which refers to the divorce procedures regulated in Articles 39–41 of the Republic of Indonesia Law No. 1 of 1974 concerning marriage and Government Regulation No. 9 of 1974 concerning the Implementation of the Marriage Law, and in Articles 129–148 KHI. The legal consequences of Qabla al-Dukhul's divorce are discussed in decision number 306/Pdt.G/2019/PA. SJ do not have legal consequences due to the dissolution of the marriage because the husband did not sue, the marriage had only lasted 7 days, and the wife left her husband and did not want to return. Again. The judges' considerations in deciding divorce cases are guided by Article 39 of the Republic of Indonesia Law No. 1 of 1974 concerning marriage, the opinion of fiqh experts in the book al-Iqna Juz II, page 133, and Qaidah Fiqhiyah. Based on these basic considerations, the author can conclude that decision number 306/Pdt.G/2019/PA Sj has taken philosophical, juridical, and sociological considerations in accordance with justice, expediency, and legal certainty.